Rasio Keuangan Dalam Menilai Kinerja Lembaga Perkreditan Desa Di Buleleng - Ni Nyoman Juli Nuryani (ARTHA SATYA DHARMA, 2021)
This study aims to analyze the value of BOPO, CAR, and NPL on the value of ROA. The type of data used is quantitative data sourced from the financial statements of the Penglatan Traditional Village LPD from 2016 to 2020. In analyzing the data, the data analysis technique used is Multiple Linear Regression Analysis, which is intended to determine the strength of the relationship, determine the effect simultaneously and finally to find out the partial relationship between the independent variable and the dependent variable. Where the BOPO, CAR, and NPL ratios are used as independent variables and the ROA ratio is used as the dependent variable. Based on the analysis that has been done, the result that: first test the model through the analysis of the coefficient of determination (R2) obtained the strength of the relationship Adjusted R Square of 0.387 or 38.7% ROA LPD Penglatan Village People affected by the variation of the three independent variables used. Second, from the F test (simultaneous test), the results show that BOPO, CAR, and NPL together have a significant positive effect on ROA. Third, through the T test, the results show that BOPO has a negative and insignificant effect on ROA, CAR has a negative and insignificant effect on ROA, and NPL has a negative and insignificant effect on ROA.